Primary prevention of peri‐implantitis: Managing peri‐implant mucositis. (April 2015) - Jepsen, Søren; Berglundh, Tord; Genco, Robert; Aass, Anne Merete; Demirel, Korkud; Derks, Jan; Figuero, Elena; Giovannoli, Jean Louis; Goldstein, Moshe; Lambert, France; Ortiz‐Vigon, Alberto; Polyzois, Ioannis; et al.
Abstract: Aims: Over the past decades, the placement of dental implants has become a routine procedure in the oral rehabilitation of fully and partially edentulous patients. However, the number of patients/implants affected by peri‐implant diseases is increasing. As there are – in contrast to periodontitis – at present no established and predictable concepts for the treatment of peri‐implantitis, primary prevention is of key importance. The management of peri‐implant mucositis is considered as a preventive measure for the onset of peri‐implantitis. Therefore, the remit of this working group was to assess the prevalence of peri‐implant diseases, as well as risks for peri‐implant mucositis and to evaluate measures for the management of peri‐implant mucositis. Methods: Discussions were informed by four systematic reviews on the current epidemiology of peri‐implant diseases, on potential risks contributing to the development of peri‐implant mucositis, and on the effect of patient and of professionally administered measures to manage peri‐implant mucositis. This consensus report is based on the outcomes of these systematic reviews and on the expert opinion of the participants. Results: Key findings included: (i) meta‐analysis estimated a weighted mean prevalence for peri‐implant mucositis of 43% (CI: 32–54%) and for peri‐implantitis of 22% (CI: 14–30%); (ii) bleeding on probing is considered as key clinical measure to distinguish between peri‐implant health and disease; (iii) lack of regular supportive therapy in patients with peri‐implant mucositis was associated with increased risk for onset of peri‐implantitis; (iv) whereas plaque accumulation has been established as aetiological factor, smoking was identified as modifiable patient‐related and excess cement as local risk indicator for the development of peri‐implant mucositis; (v) patient‐administered mechanical plaque control (with manual or powered toothbrushes) has been shown to be an effective preventive measure; (vi) professional intervention comprising oral hygiene instructions and mechanical debridement revealed a reduction in clinical signs of inflammation; (vii) adjunctive measures (antiseptics, local and systemic antibiotics, air‐abrasive devices) were not found to improve the efficacy of professionally administered plaque removal in reducing clinical signs of inflammation. Conclusions: Consensus was reached on recommendations for patients with dental implants and oral health care professionals with regard to the efficacy of measures to manage peri‐implant mucositis. It was particularly emphasized that implant placement and prosthetic reconstructions need to allow proper personal cleaning, diagnosis by probing and professional plaque removal.